2007
DOI: 10.1080/01421590701589193
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with different integration strategies of case-based e-learning

Abstract: As best practice we recommend a voluntary integration strategy combined with exam-relevance of the content. The assets and drawbacks of all described strategies are discussed in the conclusions of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 15 publications
4
71
0
4
Order By: Relevance
“…(Cook & Dupras, 2004) as step 7 of developing e-learning courses, it is not enough to assume that students will use offered e-learning resources without enhancing their participation. This is in line with many other studies (Hege et al, 2007), (Baumlin et al, 2000), (Cahill et al, 2002). The three major aspects mentioned by Cook are the accessibility and user-friendliness of the system/website, the provision of extra time ("protected" time) for the learners to complete the course and the inclusion of a reward and/or consequences mechanism.…”
Section: Vp Implementation Scenarios Into the Curriculumsupporting
confidence: 62%
See 2 more Smart Citations
“…(Cook & Dupras, 2004) as step 7 of developing e-learning courses, it is not enough to assume that students will use offered e-learning resources without enhancing their participation. This is in line with many other studies (Hege et al, 2007), (Baumlin et al, 2000), (Cahill et al, 2002). The three major aspects mentioned by Cook are the accessibility and user-friendliness of the system/website, the provision of extra time ("protected" time) for the learners to complete the course and the inclusion of a reward and/or consequences mechanism.…”
Section: Vp Implementation Scenarios Into the Curriculumsupporting
confidence: 62%
“…It could, for example, be used to compliment a face-to-face teaching unit. But, as mentioned above, without encouragement the participation of learners the use of the VP will be very low (Hege et al, 2007). Therefore, for example, Fischer et al recommend the proper integration of computer-based cases into a face-to-face learning curriculum in combination with the assessment framework (Fischer et al, 2005a).…”
Section: Vp Implementation Scenarios Into the Curriculummentioning
confidence: 99%
See 1 more Smart Citation
“…As well as engaging clinicians in the process, student engagement is also essential to allow smooth integration of an e-learning tool. A manner of strategies exist to facilitate integration [21], including:…”
Section: Resultsmentioning
confidence: 99%
“…• Studies regarding its place in the curriculum Studies have shown that designs that are associated with seminars, courses and corresponding tests [40], that are balanced [41] and appropriately integrated into the curriculum [42] all motivate students. Edelbring emphasized the importance of assessing VP-based activities not as separate phenomena but as an integrated whole together with other educational activities [42].…”
Section: Vp Designsmentioning
confidence: 99%